2016
DOI: 10.17265/2332-7839/2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 3D Methods for Identifying the Stance Phase in Treadmill Running for Both Rearfoot and Forefoot Runners

Abstract: Abstract:We compared six 3D methods, OptoGait, and Myotest Run for the determination of contact time for runners with different foot strike patterns. Twenty male participants were divided into two groups: the heel group, who attack the ground with the heel (n = 12), and the toe group, who attack the ground with the middle/front of the foot (n = 8). They performed trials at speeds of 8 km/h then 16 km/h. To detect foot strike, the use of peak velocity of 3D markers located on the heel, the fifth metatarsal, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…These differences may be attributed to our testing running speeds. Our participants were not professional runners and at the moment the study was carried out they ran two/three times per week and not much more than 10 km per week, so our testing speeds were lower than those used in most investigations with runners and, as it is well known, the swing phase becomes proportionately longer and the stance phase shorter as the speed increases (Deflandre, et al, 2016;Kharb, et al, 2011;Muñoz, et al, 2018;Nicola & Jewison, 2012;Novacheck, 1998;Rubinstein, et al, 2017;Smith & Hanley, 2013). However, our results are similar to those calculated with the data provided by López-Gómez et al (2020) even if their soccer players run at a higher speed but it may be explained by the different running pattern due to the different running surfaces (Ariza-Viviescas, et al, 2021;López-Gómez, et al, 2020) or by the fact that they were children with a lower height which undoubtedly reduces the stance phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences may be attributed to our testing running speeds. Our participants were not professional runners and at the moment the study was carried out they ran two/three times per week and not much more than 10 km per week, so our testing speeds were lower than those used in most investigations with runners and, as it is well known, the swing phase becomes proportionately longer and the stance phase shorter as the speed increases (Deflandre, et al, 2016;Kharb, et al, 2011;Muñoz, et al, 2018;Nicola & Jewison, 2012;Novacheck, 1998;Rubinstein, et al, 2017;Smith & Hanley, 2013). However, our results are similar to those calculated with the data provided by López-Gómez et al (2020) even if their soccer players run at a higher speed but it may be explained by the different running pattern due to the different running surfaces (Ariza-Viviescas, et al, 2021;López-Gómez, et al, 2020) or by the fact that they were children with a lower height which undoubtedly reduces the stance phase.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the stance phase and the float phase varies with speed. As speed increases the stance phase becomes shorter and the swing phase longer (Deflandre, Schwartz, Weerts, Croisier, & Bury, 2016;De Wit, et al, 2000;Kharb, et al, 2011;Muñoz, García, Soto, & Latorre, 2018;Nicola & Jewison, 2012;Novacheck, 1998;Rubinstein, et al, 2017;Smith & Hanley, 2013). Thus, in running, typical swing times contribute between 64 and 78% of the running gait cycle's duration, dependent on speed (Lohman, et al, 2011;Novacheck, 1998;Smith & Hanley, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We chose to use 3D analysis as it provides a precise record of the runner’s kinematics ( Deflandre et al, 2016 ) and we needed accurate data on biomechanics of the entire stride. This method of analysis requires the subject to run on a treadmill; however, running reliability should be similar in the field and on a treadmill (Hopkins et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…reduction in stride frequency (Hunter and Smith, 2007), reduction in stance duration ( Degache et al, 2013 ) and increase in knee flexion at impact (Kellis and Liassou, 2009; Mizrahi et al, 2000 )). It has previously been shown that foot location at impact varies considerably between individuals ( Delgado et al, 2013 ; Lieberman et al, 2010 ); for instance, a distinction has been drawn between heel-striking and toe-striking runners ( Deflandre et al, 2016 ; Gruber et al, 2013 ). Our results suggest that the evolution of impact location is also highly individually variable and does not follow the same pattern in each trial (ICC = .04; positive slopes for the first and second trials and a negative slope for the third trial).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation